Development of low-cost plant probiotic formulations of functional endophytes for sustainable cultivation of Coleus forskohlii - Mastan, Anthati; Rane, Digeshwar; Dastager, Syed; VivekBabu, C. S. (Microbiological Research, 2019)
Deployment of plant endophytes at field level is reported to make an impact on agricultural crop productivity; development and deployment of suitable crop specific plant probiotics in a suitable delivery matrix is a value-added task. In our study, we attempted to develop bioformulations of native, fungal endophytes of Coleus forskohlii to improve plant yield using two different carrier-based materials (talc and wheat bran). Initially, fungal endophytes (RF1, SF1, and SF2) were grown on sterilized wheat bran under solid state condition and their growth kinetics and pattern were analyzed by ergosterol content and scanning electron microscope, respectively. 10-day-grown fungal endophytic cultures were used for the development of two types of formulations (wheat bran and talc-based formulations) and tested for their efficacy on host plant, C. forskohlii under field conditions. Interestingly, application of wheat bran-based endophytic formulations significantly (p < 0.01) enhanced plant height (12-29%), number of branches (51-63%), root biomass (26-33%), photosynthetic pigments (32-101%), and forskolin content (35-56%) compared to talc-based formulations under field conditions. Shelf life of endophytes (RF1, SF1, and SF2) in both formulations revealed spore viability in wheat bran-based formulations for 6 months storage period as compared to talc-based formulations. Overall, the present investigation envisages developing plant probiotic bioformulations of functional endophytes of C. forskohlii to enhance root biomass and in planta forskolin content.

Draft genome sequence of freshwater-derived streptomyces sp. strain BPSDS2, isolated from damte stream, northeast India - Zothanpuia; Passari, Ajit Kumar; Deka, Vinay; Rajput, Lakshmi P. M.; Priya, Purbajyoti; Dharne, Mahesh; Dastager, Syed; Mathew, Oommen K.; Hashem, Abeer; Abd_ Allah, Elsayed Fathi; Singh, Bhim Pratap (American Society for Microbiology, 2019)
We report the draft genome sequence of Streptomyces sp. strain BPSDS2, isolated from freshwater sediments in Northeast India. The draft genome has a size of 8.27 Mb and 7,559 protein-coding sequences.

Deciphering the comprehensive microbiome of glacier-fed Ganges and functional aspects: implications for one health - Samson, Rachel; Kumar, Shubham; Dastager, Syed; Khairnar, Krishna; Dharne, Mahesh (Microbiology Spectrum, 2025)
Glacier-fed rivers are significant ecological components of the river catchments, yet their microbial diversity and the associated antimicrobial potential remain underexplored. The Ganges is a glacier-fed river of immense cultural, religious, and ecological significance that supports over 400 million people downstream, providing essential water for agriculture, industry, and daily use. Despite its importance, the microbial community composition and antimicrobial potential, across its relatively pristine origin, remain largely underexplored. One possible explanation for this could be the lower microbial load in the upstream glacier-fed region, which likely results in a reduced DNA yield, insufficient for whole-metagenome sequencing, in contrast to the more biologically diverse and nutrient-rich lower reaches. In this study, we developed an efficient DNA extraction and amplification method using low-input DNA to sequence the microbiome from sediments of the glacier-fed Ganges River in pre-monsoon and post-monsoon over 2 years. Taxonomic and functional diversity of bacterial and viral (phage) communities were analyzed, together with the seasonal variations in their composition. Significant differences in microbial communities were observed in response to seasonal shifts (P < 0.05). During the dry season, Proteobacteria and Actinobacteria were predominant, while Bacteroidetes and Firmicutes were abundant post-monsoon (P < 0.05). The microbiome harbors potential for the biosynthesis of streptomycin, phenylpropanoid, penicillin, and cephalosporins. Bacteriophages from Podoviridae, Myoviridae, and Siphoviridae showed lytic potential against putrefying and pathogenic bacteria. This first comprehensive study on the glacier-fed Ganges River highlights significant seasonal shifts in microbial diversity. The initial insights into the functional profile of the bacterial and phage diversity offer opportunities to explore various natural compounds and enzymes to tackle antimicrobial resistance under the one-health canopy.
Keywords: Bacteriophages; glacier-fed-Ganges; Microbiome; Secondary metabolites; special properties